On the Energy Release Rate at the Crack Tips in a Finite Pre-Strained Strip - Akbarov, Surkay D.; Turan, Arzu (TECH SCIENCE PRESS, 2011)
The influence of the initial finite stretching or compressing of the strip containing a single crack on the Energy Release Rate (ERR) and on the SIF of mode I at the crack tips is studied by the use of the Three-Dimensional Linearized Theory of Elasticity. It is assumed that the edges of the crack are parallel to the face planes of the strip and the ends of the strip are simply supported. The initial finite strain state arises by the uniformly distributed normal forces acting at the ends of the strip. The additional normal forces act on the edges of the crack. The elasticity relations for the strip material are given by the harmonic type potential. The corresponding boundary-value problem is solved by employing FEM. The numerical results on the influence of the initial finite strain state the values of the ERR and of the SIF of mode Tare presented. In particular, it is established that the values of the ERR and of the SIF of mode I decrease (increase) monotonically with an increase (decrease) in the initial stretching (compression).
Keywords: Crack; Energy Release Rate; finite initial strain; harmonic type potential; Stress Intensity Factor of mode I; strip; INTERFACE CRACKS; INITIAL STRESSES; PLATE-STRIP; Computer Science; Materials Science